Towards Teaching With an Open Heart - Walsh, Susan (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
In this paper, I explore practices for opening the heart and offering compassion towards others and also myself in the context of teaching. In doing so, I reflect upon experiences that involve the uneven distribution of “air time” in the classroom; I concentrate on such experiences because, as long-standing sources of irritation for me, I believe they can evoke insights about being present. How, for example, might I invite deeper awareness of my own being in such situations, notice how I am feeling in relation to the students, individually and collectively? How might I become better acquainted with my own resistances? Send love and compassion towards the students and also myself? Through contemplative practice, I observe my mind and habits of being. My aspiration is to teach from a softer, gentler place. I situate this work in relation to the literature in contemplative education, specifically that which offers insights into teachers’ inner work.